Aluminoxane co-catalysts for the activation of a bis phenoxyimine titanium (IV) catalyst in the synthesis of disentangled ultra-high molecular weight polyethylene. (15th September 2015) - Romano, Dario; Andablo-Reyes, Efren; Ronca, Sara; Rastogi, Sanjay
Abstract: New activation systems for the bis[ N -(3- tert -butylsalicylidene)pentafluoroanilinato] Ti (IV) dichloride catalyst (FI) for the synthesis of ultra-high molecular weight polyethylene (UHMWPE) with reduced entanglement density are explored. Together with the well-studied FI catalyst-methylaluminoxane (MAO) catalytic system, different aluminoxanes, namely polymethylaluminoxane-improved performance (PMAO), modified methylaluminoxane type 12 (MMAO12) and type 3A (MMAO3A) have been used. The catalyst activity increases with the addition of a co-catalyst modifier (2, 6-di- tert -butyl-4-methylphenol, BHT). For an example when using MMAO3A as co-catalyst in combination with BHT the catalyst activity increases by tenfold. The synthesized UHMWPEs have been characterized via rheology, differential scanning calorimetry and uniaxial solid-state deformation to evaluate the influence that the different co-catalysts have on the catalyst activation and the entangled state of the polymer. Entanglement density increases when PMAO is used as a co-catalyst influencing the rheological response of the polymer melt and melting kinetics of nascent powder. Mechanical properties increase when MMAO12 is used in place of MMAO3A as co-catalyst. However, the earlier reported mechanical properties of UHMWPE synthesized using the FI/MAO are found to be better than those obtained using the co-catalysts investigated in this study. Graphical abstract: Highlights: The FI catalyst can be successfully activated when using MAO, PMAO and MMAO12 as co-catalysts. The synthesized UHMWPEs have M w in a range of 5 million g/mol up to 11 million g/mol. The catalytic system FI catalyst + MMAO3A shows considerably depressed catalyst activity, due to the presence of TIBAl. The BHT is capable to interact with both TMA and TIBAl protecting the catalyst from modification(s). All polymers synthesized show elastic modulus build-up in the melt suggesting that the disentangled character is achieved.